Design and implementation of an energy monitoring system for buildings based on internet of things architecture (2017)
Monitoring environmental variables in buildings is a first step to implement and provide services related to energy savings, comfort and safety among others issues. In this work we design and implement an Energy Monitoring System in order to achieve monitoring of environmental variables in buildings that use decentralized air conditioning systems. In particular, we focus on variables related with human comfort, such as room temperature, humidity, CO2 and energy consumption of the air conditioning system. The system was implemented using low cost components and an Internet of Things Architecture. The field tests show the reliability of the proposed system. © 2017, Springer International Publishing AG.